Pengaruh Budaya Organisasi, Budaya Historis dan Pemetaan Stakeholder terhadap Branding Image Lembaga Pendidikan dan Dampaknya Terhadap Kinerja Lembaga - Happy Ikmal (PROGRESSA: Journal of Islamic Religious Instruction, 2020)
The academics management element uses the term 'school effect' in a number of ways to refer to the impact of certain school policies or practices, or the effects of several interventions. The purpose of this study is to analyze the indirect effect of organizational culture, historical culture and stakeholder mapping of the educational institution's branding image through variables between institutional performance. This research was conducted at the Alumni of the Tarbiyah Raden Wijaya College of Sciences, Mojokerto City. Province, East Java, uses the quantitative explanatory research description method. Primary data is collected and processed by itself and primary data sources directly provide data to data collectors on a Likert scale. Path analysis technique is used in testing the amount of contribution (contribution) shown by the path coefficient on each path diagram of the causal relationship between variables Organizational culture (X1), historical culture (X2), stakeholder mapping (X3) to the variable performance of the institution (Y) with variable between Branding image of educational institutions (Z). Correlation and regression analysis which is the basis for calculating path coefficients with the SPSS for Windows Version 20. While the study was conducted in August 2019. The exact population is unknown, using the Cochran formula a sample of 73 respondents was taken. From the results of the study it can be concluded as follows: 1) Organizational culture has no effect on the performance of the institution. 2) Historical culture has a significant effect on the performance of institutions. 3) Stakeholder mapping has a significant effect on the performance of the institution. 4) Organizational culture has a significant effect on the branding image of educational institutions. 5) Historical culture has a significant effect on the branding image of educational institutions. 6) Stakeholder mapping has no significant effect on the educational institution's branding image. 7) Institutional performance does not significantly influence the branding image of educational institutions. 8) Organizational culture, historical culture and stakeholder mapping each directly influence the branding image of educational institutions through variables between institutional performance.